Psycho-pedagogical Analysis of a Teaching Tasks System to Develop "Medical Decision Taking" in Medicine Students - Luis Alberto Corona Martínez; Miriam Iglesias León; Alfredo Espinosa Brito (Medisur)
This article allows professors of clinical courses in the Medicine career to incorporate a number of psycho-educational and didactic elements. Those elements are necessary for the comprehension and implementation of a teaching tasks system aimed at developing in students the essential skill of "medical decision making" that all medicine doctors should master. This article complements others that have already been published. In those articles arguments can be found as to the importance of this skill, as well as the previously mentioned teaching tasks system.